2016
DOI: 10.1212/wnl.0000000000003337
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dysphagia by novel real-time MRI

Abstract: RT-MRI is safe and equally capable as VF to identify the cause of dysphagia in IBM. Advantages of RT-MRI include visualization of soft tissue, more reliable timing analysis, and lack of X-ray exposure. RT-MRI may become a routine diagnostic tool for detailed assessment of the esophagus and other moving parts of the body, facilitating longitudinal evaluations in daily practice and clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 31 publications
4
80
0
8
Order By: Relevance
“…3 The IBMFRS has been extensively used in a number of cross-sectional, natural history, and drug trials. [4][5][6][7][8][9][10][11][12] It is also the primary endpoint of the phase 2/3 study of arimoclomol in IBM that started recently (NCT02753530). There is still value in optimizing the data obtained from the scale to improve the analysis of current and future trials and allow improved comparison with previous intervention and nonintervention studies.…”
Section: Accepted 14 May 2019mentioning
confidence: 99%
See 1 more Smart Citation
“…3 The IBMFRS has been extensively used in a number of cross-sectional, natural history, and drug trials. [4][5][6][7][8][9][10][11][12] It is also the primary endpoint of the phase 2/3 study of arimoclomol in IBM that started recently (NCT02753530). There is still value in optimizing the data obtained from the scale to improve the analysis of current and future trials and allow improved comparison with previous intervention and nonintervention studies.…”
Section: Accepted 14 May 2019mentioning
confidence: 99%
“…The IBMFRS has been extensively used in a number of cross‐sectional, natural history, and drug trials . It is also the primary endpoint of the phase 2/3 study of arimoclomol in IBM that started recently (NCT02753530).…”
mentioning
confidence: 99%
“…Comparisons between control and diseased/treatment groups are crucial for establishing valid VFSS markers, but due to radiation problems we limited the number of healthy controls compared with the number of SBMA patients. More recently, real‐time MRI was reported to display dysphagia equally as well as VFSS 39. Our study results will help select quantitative measures for real‐time MRI evaluations.…”
Section: Discussionmentioning
confidence: 62%
“…Paraspinal and axial muscles may be affected, resulting in head drop and camptocormia 12. Depending on the study, oropharyngeal dysphagia is reported in up to 40–86% of IBM cases, mostly due to upper esophageal sphincter dysfunction 13, 14, 15, 16. It develops insidiously, leading to frequent choking episodes and is, alongside pneumonia as a result of immobility, considered to be a potentially fatal complication of IBM.…”
Section: Clinical Presentationmentioning
confidence: 99%